Bāṃlā bhāshāẏa arthanītira baiẏera śatabārshikī - Datta, Bhabatosh, 1911- (Sośio-Ikanamika Risārca Inasṭiṭiuṭa, 1978)
Bibliographical survey of Bengali works in economics published during the latter part of the 19th century.